2008
DOI: 10.1038/sj.bjc.6604714
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus detection in Guthrie cards from paediatric leukaemia cases and controls

Abstract: Archived neonatal blood cards (Guthrie cards) from children who later contracted leukaemia and matched normal controls were assayed for adenovirus (AdV) C DNA content using two highly sensitive methods. In contrast to a previous report, AdV DNA was not detected at a higher frequency among neonates who later developed leukaemia, when compared with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…These results lead us to conclude that adenovirus DNA is not readily detected in the archived neonatal blood spots, irrespective of whether the subject subsequently develops leukaemia. Although the findings reported here fail to support our previously reported preliminary results (Gustafsson et al, 2007), these findings agree with those reported subsequently (Vasconcelos et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results lead us to conclude that adenovirus DNA is not readily detected in the archived neonatal blood spots, irrespective of whether the subject subsequently develops leukaemia. Although the findings reported here fail to support our previously reported preliminary results (Gustafsson et al, 2007), these findings agree with those reported subsequently (Vasconcelos et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…We recently reported that adenovirus DNA was detected in 13 of 51 Guthrie cards from ALL patients, but in only 6 of 47 healthy controls (P ¼ 0.0122, Fisher's exact test), indicating that adenovirus may be such a causative agent (Gustafsson et al, 2007). However, a subsequent study of twice as many paediatric ALL patients in California failed to find adenovirus DNA in the corresponding neonatal blood spots (Vasconcelos et al, 2008). This study sought to further examine the possibility of an association between prenatal adenovirus infection and ALL using a larger number of archived Swedish samples from children who later developed ALL and controls without the disease.…”
mentioning
confidence: 99%
“…In contrast to the study of cord blood lymphocytes described here, most studies evaluating neonatal blood spots have failed to detect a variety of viruses [36] including adenovirus [11,12]. The detection of adenoviral DNA in dried blood spots faces several limitations.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the fact that environmental triggers have been proposed as part of the etiology for childhood leukemia for quite sometime, limited supportive data exist [44]. Investigations of viral infection in sporadic, unclustered childhood leukemia cases have not implicated any specific infections in such populations [45–49], but specific infections have not been adequately addressed in any leukemia cluster investigation. The spike in incident military childhood ALL cases during the same time period as the Fallon cluster support the hypothesis that a specific virus was introduced into the community by the large yearly influx of military personnel training at the base that was then transmitted/amplified by the mosquito population.…”
Section: Discussionmentioning
confidence: 99%